KARAKTERISTIK BERAS ANALOG INSTAN DARI TEPUNG SORGUM (Sorghum bicolor L) PRAGELATINISASI DENGAN PENAMBAHAN TEPUNG DAUN KELOR (Moringa oleifera) - Faturochman, Hadi Yusuf; Ismaya, Pandu Legawa; Hasani, Resti Putri; Alfatah, Reza Fikri; Nur'alina, Ina (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Processing sorghum into analog rice can be one way to reduce the need for rice in Indonesia. The development of sorghum analog rice into instant analog rice products is an alternative to increase the use value of sorghum analog rice. Modification of sorghum flour by pregelatinization was carried out to improve the amylographic properties of sorghum starch so that it has characteristics suitable for instant food products. Moringa leaf flour can be added to improve the organoleptic and physico-chemical characteristics of the instant analog rice produced. The purpose of this study was to determine the organoleptic, physical and chemical characteristics of instant analog rice made from pregelatinized sorghum flour with the addition of Moringa leaf flour. This study used a completely randomized design (CRD) consisting of five comparison treatments of pregelatinized sorghum flour with Moringa leaf flour. The best treatment was determined based on the results of the highest physical characteristics and organoleptic assessment. Instant analog rice with the addition of 2.5% Moringa leaves was chosen as the best treatment because it has a low degree of breakage value (2.16%), short rehydration time (4.4 minutes), high rehydration capacity (273.75%), and has the highest organoleptic value preferred by the panelists. Based on the independent t test analysis (P<0.05), the treatment of Moringa leaf flour as much as 2.5% was able to increase the protein content (10.40%) of the instant analog rice produced.